A scoring system for predicting the risk of breast cancer-related lymphedema - Fenglian Li; Qian Lu; Sanli Jin; Quanping Zhao; Xueying Qin; Shuai Jin; Lichuan Zhang (Elsevier, 2020)
Objective: We aimed to establish a scoring system to predict the risk of breast cancer-related lymphedema. Methods: From April 2017 to December 2018, 533 patients who previously underwent surgery for breast cancer were enrolled in this cross-sectional study. Univariate analysis was performed to explore and define the risk factors. A scoring system was then established on the basis of odds ratio values in the regression analysis. Results: The additive scoring system values ranged from 6 to 22. The receiver operating characteristic (ROC) curve of this scoring system showed a sensitivity and specificity of 83.3% and 57.3%, respectively, to predict the risk of lymphedema at a cut-off of 15.5 points; the area under the curve was 0.736 (95% confidence interval: 0.662-0.811), with χ2 = 5.134 (P = 0.274) for the Hosmer-Lemeshow test. Conclusions: The predictive efficiency and accuracy of the scoring system were acceptable, and the system could be used to predict and screen groups at high risk for breast cancer-related lymphedema. Keywords: Breast cancer lymphedema, Breast neoplasms, China, Cross-sectional studies, Lymphedema, Risk factors, ROC curve